CLIMATE CHANGE ADAPTATION AND RESILIENCE STRATEGIES FOR HYDRAULIC STRUCTURES IN THE RIVERS OF UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2025)
This study investigates the vulnerability and adaptation potential of hydraulic infrastructure in Uzbekistan's river systems under changing climatic conditions. With a focus on major rivers such as the Amu Darya and Syr Darya, the paper evaluates projected hydrological alterations due to climate change, assesses the risks to existing hydraulic structures, and proposes strategic interventions for their sustainable management. A combination of climate modeling, hydrological simulation, and infrastructure resilience analysis is employed. The findings reveal a substantial need for adaptive design upgrades, institutional coordination, and integrated water resource management to safeguard Uzbekistan's water security.